Equilibrium Analyses in Aqueous Solution under Accompanying Side Reactions by Capillary Zone Electrophoresis - TAKAYANAGI, Toshio (BUNSEKI KAGAKU, 2015)
Analysis methods of equilibrium in an aqueous solution have been developed by capillary zone electrophoresis (CZE) utilizing its separation principle. The equilibrium of interest has been analyzed by affinity capillary electrophoresis (ACE) through the change in the electrophoretic mobility. Coexisting substances including degraded compounds are resolved from the equilibrium species by CZE, and an acid dissociation constant of photo-degradable haloperidol was determined in the presence of the degraded substances. In addition to the classical CZE separation, it has been noticed that gradually generated substances during CZE are resolved from the equilibrium species, and that the generated substances are observed as a leading/tailing signal to the equilibrium species. Slowly generated species from phenolphthalein by the addition of OH− in an alkaline pH solution was resolved from the equilibrium species, and the side reaction to the objective acid-base equilibria was excluded. Thus, two steps of the acid dissociation constants of phenolphthalein were determined by ACE. The acid-base equilibrium of tetrabromophenolphthalein ethyl ester (TBPE) was also analyzed by CZE under the degrading conditions, although the hydrolysis of the ester moiety accompanies with TBPE in acidic pH conditions. The precipitation reaction as a side reaction can also be excluded in the CZE analysis. The low concentration of analyte below its solubility is detected as a usual CZE signal, and the equilibrium of interest can be analyzed. The ion-association constants of dipicrylaminate ion with pairing cations were determined by ACE. Even under precipitating conditions, the precipitate is resolved from the equilibrium species by CZE, and it is dissolved again in the separation buffer. Acid dissociation constants of tetrabromophenolphthalein are determined by ACE under precipitable conditions. It was demonstrated in this study that the utilization of the CZE separation is advantageous on equilibrium analysis by ACE to such reactions as to be degradable and precipitable ones, compared to the ordinary analysis in homogeneous solutions, including potentiometric and photometric titrations.